The effect of probiotic, prebiotic, and synbiotic supplements on anthropometric measures and respiratory infections in malnourished children: a systematic review and meta-analysis of randomized controlled trials - Masoumeh Paiandeh; Mahsa Maghalian; Sakineh Mohammad-Al; Mojgan Mirghafourvand (BMC, 2024)
Abstract Background Malnutrition remains a significant concern in many societies. This study systematically reviewed the effects of probiotics, prebiotics, and synbiotics on anthropometric measures in malnourished children, focusing on changes in weight, height, and respiratory infections (primary outcomes), and head circumference, hemoglobin, hematocrit, and body mass index (BMI) as secondary outcomes. Methods This systematic review and meta-analysis involved searching various databases in both Persian and English, including Scopus, Web of Science Core Collection, Cochrane Library, Science Direct, and PubMed up to October 5, 2024. Non-randomized controlled trials (RCTs) were excluded. The Cochrane Handbook Risk of Bias Version 2 tool was used to assess risk of bias, and RevMan 5.3 software was employed for analysis. Subgroup analyses were conducted based on the type of supplement received. Meta-regression was applied to identify factors influencing results, and the GRADE approach was used to evaluate evidence certainty. Results Twelve studies with a total of 3,086 children (aged up to 6 years, equally distributed between boys and girls) were included. All children were malnourished without underlying illnesses. Limitations of the study included variations in intervention type, dose, duration, and timing of outcome measurement. Meta-analysis revealed that probiotics, prebiotics, and synbiotics may increase weight (6 trials, mean difference: 0.33 kg, 95% CI: 0.15 to 0.50, low certainty of evidence), while probiotics and synbiotics may increase height compared to control groups (5 trials, mean difference: 0.44 cm, 95% CI: 0.02 to 0.85, low certainty of evidence). However, probiotics and synbiotics did not show a statistically significant effect on lower respiratory tract infections (5 trials, risk ratio: 0.84, 95% CI: 0.68 to 1.04, moderate certainty of evidence). Meta-regression indicated that intervention type, sample size, and follow-up duration were not significant moderators for outcomes related to weight, height, or respiratory infections. Conclusion The current evidence suggests that probiotics, prebiotics, and synbiotics supplements may help manage malnutrition-related outcomes in malnourished children, but further research with stronger study designs is needed to confirm these findings due to the low certainty of evidence.